Fractionation of phenolic compounds from Sonneratia apetala pneumatophores and their bioactivities - Mai, Nguyen Sao; Tan, Dao Van (Academia Journal of Biology, 2017)
Sonneratia apetala pneumatophore samples were collected from Xuan Thuy National Park, and then 80% methanol extract was fractionated through Sephadex LH-20 column chromatography. After elution with 95% ethanol and 50% acetone, two phenolic fractions were obtained from the crude extract of of S. apetala pneumatophore. The acetone fraction consisted of tannins having high antioxidant activity, 1.14 times higher than that of ascorbic acid. This fraction also have higher activity of α-amylase inhibition (IC50 0.83 mg/mL) and R. sativus root growth inhibition (IC50 6.4 mg/mL) than did the ethanol fraction. In contrast, ethanol fraction consisted of low-molecular phenolic compounds having inhibitory effects on Samonella tiphimurium growth. Such antibacterial activity was not observed in the acetone extract. Citation: Nguyen Sao Mai, Dao Van Tan, 2017. Fractionation of phenolic compounds from Sonneratia apetala pneumatophores and their bioactivities. Tap chi Sinh hoc, 39(4): 451-456. DOI: 10.15625/0866-7160/v39n4.10708. *Corresponding author: daotanvn@yahoo.com Received 19 September 2017, accepted 12 December 2017